Crystal structure of {(but-3-en-1-yl)bis[(pyridin-2-yl)methyl]amine-κ3N, N′, N′′}dichloridocopper(II) diethyl ether hemisolvate. (2015) - Bussey, Katherine A.; Connell, Jennifer R.; McGlone, Annie R.; Mraz, Margaret E.; Oshin, Kayode D.; Pintauer, Tomislav; Oliver, Allen G.
No abstract available